EVALUASI USABILITY PADA LEARNING MANAGEMENT SYSTEM PERGURUAN TINGGI MENGGUNAKAN USER EXPERIENCE QUESTIONNAIRE - Wynand Heskia Rahangmetan; Melkior N. N. Sitokdana (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
In the digital era, the use of technology in education is a must, such as a Learning Management System (LMS). Satya Wacana Christian University (UKSW) implemented the Flexible Learning (FLEARN) programme to facilitate learning. This research evaluates the usability of the LMS using the User Experience Questionnaire (UEQ) method. A UEQ questionnaire with 26 attributes and a 7-point rating scale was distributed via Google Form to WKSW students. The data was analysed using Cronbach Alpha coefficient and interpretation of the results of each attribute. The results showed that the mean scores of the six UEQ scales: attractiveness (1.442), clarity (1.722), efficiency (1.838), accuracy (1.314), stimulation (1.209), and novelty (0.856). The efficiency scale has the highest score, indicating that FLEARN UKSW is efficient in learning, while novelty has the lowest score, indicating a lack of innovation. Only the efficiency scale is categorised as good, while the other scales are above average, so the usability of FLEARN UKSW is good, but improvements are needed on navigation, visual quality, and readability of the LMS text. The research results are expected to be a reference for the future development of FLEARN UKSW.